Automotive brake systems - Owen, Clifton E. (Thomson Delmar Learning, 2008)
The newest edition of Today's Technician: Automotive Brake Systems continues to provide outstanding coverage of the theory and repair procedures related to automotive brakes. Students, entry-level technicians, and experienced technicians alike will benefit from the two-volume approach: a Classroom Manual to detail the theories and application of the total brake system, sub-system, and components, combined with a corresponding Shop Manual to provide real-world symptoms, diagnostics, and repair information about these systems. Automotive Brake Systems, 4E will help prepare readers for the ASE (A5) certification exam, as well, with ASE Challenge questions at the end of each chapter of the Shop Manual, and a Practice Exam in the Appendix. Major updates in this edition include coverage of the latest materials used in brake systems, current electronics, and an expanded but more general coverage of electric braking systems, so users don't get bogged down with highly detailed, manufacturer-specific information. Together, the Classroom and Shop Manuals offer all the information needed to understand, diagnose, and repair most problems that could occur with today's brakes systems